Teleconsultation contribution to hospital patient satisfaction: Bibliometric analysis - Tini Ariyati; Sri Sundari (Universitas Aisyah Pringsewu, 2023)
During the COVID-19 pandemic, telemedicine is considered a health service solution. Teleconsultation is an innovation that makes it easy for patients to consult with specialist physicians without having a face-to-face meeting. This study aims to determine developments related to research on the effectiveness of teleconsultation in an effort to increase patient satisfaction. The research results can be implemented to improve post-pandemic teleconsultation services, whether this teleconsultation is still needed. Methods: research using quantitative methods with a bibliometric analysis approach. The literature used is based on journal articles obtained through the Scopus database. Using the VOSviewer software, the results of a literature search conducted through the Scopus database were also visually evaluated. Result: Based on an analysis of the year of publication of the contribution of teleconsultation to patient satisfaction, a total of 673 publications were successfully entered into the Scopus database in the period 2018-2022. The most commonly used method commonly used method is controlled study. Conclusion: the level of satisfaction with teleconsultation services needs to be measured by conducting another study during the post-pandemic period, where face-to-face meetings were no longer restricted. Is there still a need for teleconsultation for now.